2022
DOI: 10.3390/mi13040561
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Skin Wound Healing Using Flexible Photovoltaic-Bioelectrode Electrical Stimulation

Abstract: Owing to the complex and long-term treatment of foot wounds due to diabetes and the limited mobility of patients, advanced clinical surgery often uses wearable flexible devices for auxiliary treatment. Therefore, there is an urgent need for self-powered biomedical devices to reduce the extra weight. We have prepared an electrically stimulated MEMS (Micro Electromechanical System) electrode integrated with wearable OPV (Organic photovoltaic). The wearable OPV is constructed of a bio-affinity PET-ITO substrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…21 Furthermore, research has shown that combining electroactive materials with electrical stimulation might have a synergistic effect, improving therapeutic efficacy in skin injury. 22 We observed that DOPA-PonG1@CS/rGO materials exhibited superior cell viability and adhesion capabilities compared to unmodified CS materials likely due to the increased expression of genes required for tissue repair including matrix protein (Col1) and angiogenesis (VEGF). We identified that application of 100 mV electrical stimulation was most effective in stimulating cell viability, and when electrical stimulation was combined with DOPA-PonG1@CS/rGO materials, there was further acceleration in wound healing.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…21 Furthermore, research has shown that combining electroactive materials with electrical stimulation might have a synergistic effect, improving therapeutic efficacy in skin injury. 22 We observed that DOPA-PonG1@CS/rGO materials exhibited superior cell viability and adhesion capabilities compared to unmodified CS materials likely due to the increased expression of genes required for tissue repair including matrix protein (Col1) and angiogenesis (VEGF). We identified that application of 100 mV electrical stimulation was most effective in stimulating cell viability, and when electrical stimulation was combined with DOPA-PonG1@CS/rGO materials, there was further acceleration in wound healing.…”
Section: Discussionmentioning
confidence: 85%
“…Electrical microcurrent treatment uses low intensity (μA) currents that are comparable to endogenous electric fields produced during wound healing, and supports the formation of extracellular matrix proteins whose formation and diffusion promote cell adhesion and proliferation 21 . Furthermore, research has shown that combining electroactive materials with electrical stimulation might have a synergistic effect, improving therapeutic efficacy in skin injury 22 . We observed that DOPA‐PonG1@CS/rGO materials exhibited superior cell viability and adhesion capabilities compared to unmodified CS materials likely due to the increased expression of genes required for tissue repair including matrix protein (Col1) and angiogenesis (VEGF).…”
Section: Discussionmentioning
confidence: 86%
“…ultrasound) have been published (47). Also, wearable flexible devices facilitating electrostimulation for the healing of foot wounds are at different stages of development and even home-based systems as a supportive therapy to speed up the healing process have been tested (48,49). Furthermore, electrostimulatory systems to improve mobilisation and walking abilities of patients with diabetes following minor amputations have been tested and shown encouraging results (50).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Based on this, efforts to further improve and optimize the results of electrical stimulation are in progress and promising results on the effectiveness of combination of electrical stimulation with other noninvasive measures (e. g., ultrasound) have been published 47 . Also, wearable flexible devices facilitating electrostimulation for the healing of foot wounds are at different stages of development and even home-based systems as a supportive therapy to speed up the healing process have been tested 48 49 . Furthermore, electrostimulatory systems to improve mobilization and walking abilities of patients with diabetes following minor amputations have been tested and shown encouraging results 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, wearable flexible devices facilitating electrostimulation for the healing of foot wounds are at different stages of development and even home-based systems as a supportive therapy to speed up the healing process have been tested [48,49]. Furthermore, electrostimulatory systems to improve mobilization and walking abilities of patients with diabetes following minor amputations have been tested and shown encouraging results [50].…”
Section: Diabetic Foot and Electrostimulationmentioning
confidence: 99%